The Relationship between Third-generation TSH Receptor Antibody Positivity and Cumulative Methimazole Dose Used until Remission in Graves' Disease - GÖZÜ, HÜLYA (COLL PHYSICIANS & SURGEONS PAKISTAN, 2021)
Objective: To determine the relationship between the positivity of third-generation TSH receptor antibody ( TRAb) at the time of diagnosis and the cumulative methimazole dose used until remission in patients with Graves' disease. Study Design: Cross-sectional, descriptive study. Place and Duration of Study: Department of Endocrinology and Metabolic Diseases, University of Health Sciences, Kartal Dr. Lutfi Kirdar City Hospital, Turkey from 2016 to 2018. Methodology: Newly diagnosed Graves' patients were included in the study. The patients were divided into two groups according to whether they entered remission (n: 21) or not (n: 20), in the 18th month of methimazole treatment. In addition, the patients were further divided into two categories, according to TRAb status at the time of diagnosis as negative (n: 17) or positive (n: 24). The TRAb positivity and the cumulative methimazole dose they used until the month of remission were compared in these groups. Results: The mean time to reach remission in 41 patients was 20.5 +/- 3.1 months. TSH receptor antibody positivity rate was 58.5%. When the TRAb positivity of the groups was compared according to the state of having remission in the 18th month of the treatment, the positivity rate in the non-remission group was statistically significantly higher (p = 0.023).The time to go into remission was longer and the cumulative methimazole dose requirement was higher in the TRAb positive group (p <0.001). Conclusion: Graves' disease patients with positive third-generation TRAb were found to have a lower rate of remission in the 18month period compared to negative patients.
Keywords: Graves' disease; TSH receptor antibody; Cumulative; Methimazole; AMERICAN THYROID ASSOCIATION; PREDICT RELAPSE; FOLLOW-UP; HYPERTHYROIDISM; MANAGEMENT; GUIDELINES; DIAGNOSIS